Perangkat perkuliahan pembelajaran Literasi berbasis e-learning - Nurchasanah, Nurchasanah; H.S., Sunaryo (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2016)
This research aims to develop a literacy-based e-learning materials for graduate students by (1) describing the results of analyzing the syllabus, the teaching materials from course convenor, the students and the lecturers’ responses and developing the e-learning protoype material; (2) conducting an expert validation and a tryout; and (3) disseminating the product. The result of this research and development study a prototype of literacy-based teaching and learning material and its assessment for graduate students in an interactive CD applying an autoplay program.